Distribution of metals and trace elements in adult and juvenile penguins from the Antarctic Peninsula area - Jerez, Silvia (2013)
Fil: Jerez, Silvia. Área de Toxicología. Facultad de Veterinaria. Universidad de Murcia. Murcia; España